Pressurized hot water extraction of nutraceuticals and organic pollutants from medicinal plants - Mokgadi, Janes (Rhodes University, Faculty of Science, Department of Chemistry, 2011)
This thesis explores the robustness and the versatility of pressurized hot water extraction (PHWE) for a variety of analytes and matrices. Applications discussed include: selective extraction of alkaloids in goldenseal followed by their degradation studies; in-cell clean-up of pesticides in medicinal plants employing custom made molecularly imprinted polymers (MIPs) sorbents; in-cell pre-concentration followed by desorption of aflatoxins in plants with MIPs; desorption of pesticides from electrospun nanofiber sorbents; and removal of templates from MIPs sorbents. It was demonstrated that selective extractions could be achieved by just changing the temperature of water while adjusting the pressure. For instance, the alkaloids in goldenseal (hydrastine and berberine), were extracted at 140 Â°C, 50 bars, 1 mL minâ »Â¹ in 15 min; organochlorine pesticides from medicinal plants were extracted at 260 Â°C, 80 bars, 1 mL min-1 in 10 min; while aflatoxins AFG2, AFG1, AFB2 and AFB1 were extracted at 180 Â°C, 60 bars and a flow rate of 0.5 mL minâ »Â¹ in 10 min. The selectivity of PHWE was further enhanced by combining it with selective MIPs sorbents at higher temperatutes. In-cell clean-up of interfering chlorophyll was successfully removed from the medicinal plants during pesticides analysis while clean-up of aflatoxins AFG2, AFG1, AFB2 and AFB1 was achieved in two extraction cells connected in series. Ultrasound was also combined with PHWE for extraction of hydrastine and berberine at 80 Â°C and 40 bars in 30 min. PHWE was further evaluated for removal of templates from quercetin, phthalocynine and chlorophyll MIPs. The templates were thoroughly washed off their MIPs within 70 min with PHWE compared to over 8 h for Soxhlet and ultrasound assisted extraction. Pesticides were also desorbed from electrospun nanofibers at 260 Â°C, 80 bars in 10 min employing only water at 0.5 mL minâ »Â¹. In the light of green chemistry, the decrease in the usage of organic solvents was 100%, resulting in no organic solvent waste.
Keywords: Functional foods; Medicinal plants -- Biotechnology; Extraction (Chemistry); Goldenseal; Botanical pesticides; Sorbents; Organic solvents